موافقة المعجزة الخالدة للنبوة الخاتمة -دراسة عقدية - Said, R. (Universiti Sains Islam Malaysia, 2024)
Prophets of Allah were endowed with miracles as signs of their truthfulness. The prophets before Muhammad SAW were sent particularly to their people, and the miracles given to them were also temporal and physical in nature. On the contrary, the message of Muhammad SAW is eternal and universal for all mankind. As such, the miracle given to him in the form of the Quran is also eternal and suitable for all until the end of time. In this paper, discussion is focused on the Quran as the eternal miracle of Islam and important issues relating to it. In addition, definition and relation between miracle and prophethood is also analyzed. It is proposed that the Quran is the only everlasting miracle of Muhammad SAW despite other physical miracles performed by him during his lifetime.